About affect and meta-affect in mathematics education: an interview with Gerald A. Goldin Sobre afeto e meta-afeto na educação matemática: uma entrevista com Gerald A. Goldin - Comelli, Felipe Augusto de Mesquita; Manrique, Ana Lúcia (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
Researcher Gerald A. Goldin presents a trajectory in mathematics education dating back to the early 1970s. His works position him as an influential researcher, contributing to investigations in regard to systems of representation and affect related to the teaching and learning of mathematics. Our primary interest in having a dialogue with Goldin was to record his considerations about the Affective Domain, with an emphasis on meta-affect, as well as to gather his views on current and future directions for research in the field. O pesquisador Gerald A. Goldin apresenta uma trajetória na educação matemática que remonta aos primeiros anos da década de 1970. Seus trabalhos o colocam como um pesquisador influente, contribuindo com investigações sobre sistemas de representação e sobre afetos no ensino e aprendizagem de matemática. Nosso interesse principal no diálogo com Goldin foi o de registrar suas considerações sobre o Domínio Afetivo, com ênfase no meta-afeto, bem como coletar suas opiniões sobre o atual e futuro caminhos para as pesquisas na área.